Multifunctional Therapeutic Delivery Strategies for Effective Neuro-Regeneration Following Traumatic Spinal Cord Injury - Kumar, Pradeep; E. Choonara, Yahya; Modi, Girish; Naidoo, Dinesh; Pillay, Viness (Current Pharmaceutical Design, 2015)
Traumatic Spinal Cord Injuries (TSCI), due to their devastating nature, present several interventional challenges (extensive inflammation, axonal tethering, scar formation, neuronal degeneration and functional loss) that need to be addressed before even a slight neuronal recovery can be achieved. Recent post-TSCI investigational approaches include a combination of “support and therapeutic” strategies capable of providing localized delivery of therapeutic molecules along with specialized architecture to allow axonal growth and conformal repair. This review provides a brief overview of multifunctional therapeutic delivery strategies for effective neuroregeneration post-TSCI with special emphasis on intrathecal hydrogel-based injectable systems, chondroitinase ABC releasing matrices, micro/nano-sized particulate strategies, 3D-scaffold architectures, biopolymeric channeled bridges for directed neuronal growth, functionalized nerve conduits, nano- and micro-fibrous scaffolds and multicomponent combinatorial paradigms for localized delivery to spinal cord. In addition; a comprehensive account of most widely employed macromolecules and the related neuro-pharmacological, -anatomical, and -functionaloutcomes conferred by the abovementioned neural tissue engineering approaches is provided. Furthermore, the performance of individual delivery systems towards the enhancement of effectiveness, efficiency, and stability of therapeutic molecules and neurotrophic factors is discussed. In conclusion, it is suggested that a multifunctional combinatorial device assimilating the biomaterial, cellular, molecular, structural and functional aspects altogether is the best way forward for effective neuroregeneration post-TSCI.
Keywords: neurotrophic factors